(untitled) (Hilo Analítico, 2023)
The emergence of the drag phenomenon, and its continuous global growth thanks to the mass media, implies reflecting, from a critical perspective, the artistic-political aspects that compose it, as well as its possible implications for individuals and the social world. Thus, and as a product of reflections from the training in psychology and the own experience as a drag performer, an approach is made to the understanding of drag practice and performativity as an artistic-political act through which discourses, populations and controversial, censored, forbidden, rejected or unspeakable themes are criticized, expressed, made visible and given rise to, adopting both a transforming, subversive and identitarian function of the social world and individuals, as well as a possible element promoting individual and collective mental health.